An Analysis of How Online Reviews, Product Quality, and Digital Marketing Afeect Consumer Decisions to Buy on the Gunungsitoli City Tik Tok Shop Application - Asliagus Eli Lase (Universitas Negeri Semarang, 2025)
This study explores the relationship between online reviews, product quality, and digital marketing on consumer purchasing decisions on e-commerce platforms (TikTok Shop) in Gunungsitoli City. Quantitative research methods and purposive sampling techniques were used to involve 80 users of the TikTok shop application, specifically for consumers in Gunungsitoli City. The results of multiple linear regression analysis show that product quality has the most significant influence on purchasing decisions, followed by digital marketing and online reviews, which also have a considerable impact. Overall, these three variables contribute significantly to consumer purchasing decisions, with the research model able to explain most of the variation in these decisions. These findings emphasize the importance of these three aspects in the context of TikTok shop users, where product quality is the main factor influencing consumer purchasing decisions. This study's theoretical and practical implications demonstrate the importance of a multi-dimensional approach in digital marketing strategies, especially in an increasingly competitive e-commerce platform environment. This study also adds insight into the literature on consumer behavior related to modern marketing technology. It provides a strategic perspective for users of the rapidly growing TikTok shop application in Gunungsitoli City.